Aromatic L‐Amino Acid Decarboxylase Gene Therapy Enhances Levodopa Response in Parkinson's Disease. Issue 5 (9th March 2020) - Nutt, John G.; Curtze, Carolin; Hiller, Amie; Anderson, Shannon; Larson, Paul S.; Van Laar, Amber D.; Richardson, R. Mark; Thompson, Marin E.; Sedkov, Alexander; Leinonen, Mika; Ravina, Bernard; Bankiewicz, Krystof S.; et al.
Abstract: Background: As Parkinson's disease progresses, levodopa treatment loses efficacy, partly through the loss of the endogenous dopamine‐synthesizing enzyme L‐amino acid decarboxylase (AADC). In the phase I PD‐1101 study, putaminal administration of VY‐AADC01, an investigational adeno‐associated virus serotype‐2 vector for delivery of the AADC gene in patients with advanced Parkinson's disease, was well tolerated, improved motor function, and reduced antiparkinsonian medication requirements. Objectives: This substudy aimed to determine whether the timing and magnitude of motor response to intravenous levodopa changed in PD‐1101 patients after VY‐AADC01 administration. Methods: Participants received 2‐hour threshold (0.6 mg/kg/h) and suprathreshold (1.2 mg/kg/h) levodopa infusions on each of 2 days, both before and approximately 6 months after VY‐AADC01. Infusion order was randomized and double blinded. Unified Parkinson's Disease Rating Scale motor scores, finger‐tapping speeds, and dyskinesia rating scores were assessed every 30 minutes for 1 hour before and ≥3 hours after start of levodopa infusion. Results: Of 15 PD‐1101 patients, 13 participated in the substudy. Unified Parkinson's Disease Rating Scale motor score area under the curve responses to threshold and suprathreshold levodopa infusions increased by 168% and 67%, respectively, after VY‐AADC01; finger‐tapping speeds improved by 162% and 113%, and dyskinesia scores increased by 208% and 72%, respectively, after VY‐AADC01. Adverse events (mild/moderate severity) were reported in 5 participants during levodopa infusions pre–VY‐AADC01 and 2 participants post–VY‐AADC01 administration. Conclusions: VY‐AADC01 improved motor responses to intravenous levodopa given under controlled conditions. These data and findings from the parent study support further clinical development of AADC gene therapy for people with Parkinson's disease. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.